2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333996
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual feedback and speed on micromanipulation accuracy

Abstract: Accuracy in micromanipulation tasks is limited and it is important to identify various factors affecting it. This paper studies the effect of visual magnification, speed and handedness to micromanipulation accuracy using microscope and LCD screen for feedback. Magnification of visual feedback increases the accuracy, but large magnification does not provide further improvement beyond 16x. Further, we observed a trade off between speed and accuracy in tracing a circular path, i.e. faster speed reduces the speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Preliminary results with surgeons in our laboratory have suggested that viewing the workspace via cameras and computer monitor degrades performance compared to viewing directly through the stereo operating microscope [2]. There have been studies on how the micromanipulation accuracy is affected while performing tasks in microsurgery in different conditions such as posture, visual feedback, grip force, and speed [34]. However, there is a general lack of studies that analyze different display methods and their effect on micromanipulation accuracy; evaluation studies of medical augmented reality displays tend to assess only the accuracy of the image registration itself, rather than the accuracy of manipulation enabled by the display [5].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results with surgeons in our laboratory have suggested that viewing the workspace via cameras and computer monitor degrades performance compared to viewing directly through the stereo operating microscope [2]. There have been studies on how the micromanipulation accuracy is affected while performing tasks in microsurgery in different conditions such as posture, visual feedback, grip force, and speed [34]. However, there is a general lack of studies that analyze different display methods and their effect on micromanipulation accuracy; evaluation studies of medical augmented reality displays tend to assess only the accuracy of the image registration itself, rather than the accuracy of manipulation enabled by the display [5].…”
Section: Introductionmentioning
confidence: 99%